Is good design good business? - Cummings, Stephen; Petty, Margaret; Walker, Ben (School of Management Working Papers, 2012)
‘Good design’ is increasingly regarded as a vital one-size-fits-all solution to the strategic challenges of 21st century business. In the last decade many studies have promoted the importance of good design in improving firms’ attractiveness to the market and profitability, and enhancing industry productivity and economic development. In concert with this push, ‘design thinking’ has become the ‘next big thing’ in business. However, there is little hard evidence to support claims that good design is necessarily good business, with partial analysis or anecdotal reference to particular companies generally employed instead to buttress such claims. This paper contrasts the share prices of firms that have won highly regarded design awards with average share price movements in NZ, Australia, the United States and the UK. Contrary to earlier research, we found that winning design awards does not lead to above average performance in NZ, Australia or the UK. However, there was some positive effect in the US where the market listings are more internationally diverse. As a result, we raise questions about the assumption that good design is good business, and outline the implications for theory building and practice.